2018
DOI: 10.3390/ma11060924
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Glaukonite Sandstone as a Result of Alkali-Silica Reactions in Cement Mortar

Abstract: The mechanism of concrete degradation as a result of an alkali-silica reaction (ASR) largely depends on the mineral composition and microstructure of the reactive aggregate. This paper shows the reactivity results of quartz-glaukonitic sandstone, which is mainly responsible for the reactivity of some post-glacial gravels, available in Poland. After initial petrographic observations under a light microscope, the mode of sandstone degradation triggered by the reaction with sodium and potassium hydroxides was ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…In view of that, the borosilicate glass is used as a reference aggregate for tests [5,6]. In research practice, the opal aggregate composed of amorphous silica [7][8][9][10] is used more often than other, less reactive, types of aggregate to investigate concrete degradation due to ASR [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In view of that, the borosilicate glass is used as a reference aggregate for tests [5,6]. In research practice, the opal aggregate composed of amorphous silica [7][8][9][10] is used more often than other, less reactive, types of aggregate to investigate concrete degradation due to ASR [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…This is because waste glass, unlike glass fibres deliberately manufactured for use in concrete, is not coated to counteract ASR [31]. Degradation of the cement composite with waste glass is not the rule, although the results of standard expansion tests often indicate an increased different products are identified [12,46]. They may take various forms of loose gels with a "house of cards" [27,47] structure or sword-like or rosette-like morphologies [48].…”
Section: Introductionmentioning
confidence: 99%
“…However, in previous studies, the expansion of carbonate aggregates was attributed to dedolomitization [96][97][98]. Although sedimentary aggregates have a small amount of silica, research studies have shown that they can undergo ASR, which is due mainly to the presence of a small-to-appreciable amount of reactive silica [24,99]. In some non-siliceous carbonate rocks, even with low silica content, the alkali-silica reaction can occur [24,94], which was observed in the tested Bathurst limestone aggregate.…”
Section: Discussionmentioning
confidence: 99%
“…The fragmentation of the aggregate can increase the availability of aggressive ions to silica, accelerating its reaction, while larger grains probably react more slowly. As Czapik pointed out, in an analysis of the reaction of alkalis with polymineral aggregate, that the migration of alkalis in the hardened cement paste and aggregate matrix should be considered [34]. One should not overlook the changes in gel properties caused by the exchange of Na + and K + ions for Ca 2+ ions, depending on the diffusion rate of these ions.…”
Section: Macroscopic and Microscopic Examinationmentioning
confidence: 99%